AI thousand questions and answers based on large model accurately serve the personalized needs of teachers and students - ZHANG Long; ZHANG Xiang; LAI Bingheng; WANG Shangyu (Tongxin xuebao)
The system architecture of the vertical large model of education was discussed, the construction technology of the intelligent platform of “AI thousand questions and answers” of Xi’an University of Architecture and Technology was introduced, and educational application scenarios were built, such as AI question and answer, AI office, AI tools and AI robots on this basis to provide accurate services for the personalized needs of teachers and students. The “AI thousand questions and answers” intelligent platform explores the application scenarios of large model technology serving university educational affairs, scientific research and other fields, and realizes the intelligent transformation of education.